HPLC-UV-MS/MS Profiling of Phenolics from Euphorbia nicaeensis (All.) Leaf and Stem and Its Antioxidant and Anti-Protein Denaturation Activities - Khawla Bouaouda; Chaimae Elagdi; Naoufal El Hachlafi; Karima Mohtadi; Mohammed Hsaine; Anass Kettani; Rachid Flouchi; Khang Wen Goh; Abdelhakim Bouyahya; Hanae Naceiri Mrabti; Rachid Saile; Hassan Taki (Progress in Microbes and Molecular Biology)
This work focuses on the leaves and stems of Euphorbia nicaeensis All. to confirm its historical use by the Moroccan population. The phytochemical profile of the plant by HPLC-UV-MS/MS was identified for the first time, and the biological activities of each plant organ was evaluated separately by maceration and ultrasonic-assisted extraction. The evaluation of antioxidant activity based on DPPH assay and hydrogen peroxide scavenging assay showed that leaves could be used as a natural source of antioxidants as they provide a potent antioxidant effect (DPPH IC50 = 23.47±0.62 µg/ml), (H2O2 IC50 = 110.27 ± 3.59 µg/ml) compared to stems. These results were proven by HPLC-UV-MS/MS analysis and revealed that E. nicaeensis leaves are richer in phenolic compounds, especially quercetin and derivatives, known for their antioxidant properties. In contrast, the stems could be considered a potential anti-inflammatory agent considering their solid anti-inflammatory activity. The most potent effects were obtained at a concentration of 2 mg/ml, which induced 83.98% and 82.04% inhibition against bovine albumin and egg albumin denaturation, respectively, compared to the control. In addition, the stem phytochemical profile indicated the presence of some compounds with anti-inflammatory effects, such as fargesin and nuciferine. Likewise, the findings showed that ultrasound-assisted extraction was more effective than maceration.